Group reciprocity - David Hugh-Jones; Martin A. Leroch (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
People exhibit group reciprocity when they retaliate, not against the person who harmed them, but against somebody else in that person's group. Group reciprocity may be a key motivation behind intergroup conflict. We investigated group reciprocity in a laboratory experiment. After a group identity manipulation, subjects played a Prisoner's Dilemma with others from different groups. Subjects then allocated money between themselves and others, learning the group of the others. Subjects who knew that their partner in the Prisoner's Dilemma had defected became relatively less generous to people from the partner's group, compared to a third group. We use our experiment to develop hypotheses about group reciprocity and its correlates.
Keywords: D74; C92; 330; reciprocity; groups; conflict; Austauschtheorie (Soziologie); Arbeitsgruppe; Konflikt; Gefangenendilemma; Test